Smart IoT-enabled Solar Power Supervision and Regulation System - Shib Sowrov Komar; Rahman Md. Tanvir; Dipto Durjoy Roy; Shufian Abu; Zishan Md. Saniat Rahman; Basak Rinku; Mannan Md. Abdul (BIO Web of Conferences)
In today's world, transitioning to sustainable energy sources is essential due to the reduction of limiting resources and rising energy consumption. Solar energy stands out as a key renewable source, providing an eco-friendly alternative to fossil fuels by converting sunlight into electricity through photovoltaic (PV) technology. This study presents the development and assessment of a Solar Power Supervision and Regulation System designed to optimize solar energy utilization. The system incorporates a PV array connected to an Arduino Uno microcontroller, an ESP8266 Wi-Fi module for data transmission, and a Liquid Crystal Display (LCD) for real-time feedback. Collected data is transmitted to the ThingSpeak platform for storage, visualization, and analysis, enabling intelligent decision-making. This approach enhances energy efficiency and enables remote monitoring and control, lowering dependence on conventional sources of energy and lowering emissions of greenhouse gases. According to this study, this system operates with an efficiency of nearly 90% and provides users with approximately 20% energy savings. The simulation for this study was conducted using the Proteus Interface.